Cardiovascular Risk Behavior among Adolescents of Higher Secondary School in Central Nepal - Adhikari, Pratima; Paudel , Nirmala Kumari Sharma; Sapkota, Devi Kumari (Journal of National Heart and Lung Society Nepal, 2025)
Background: Cardiovascular diseases (CVDs) are the leading cause of death globally. However, most cardiovascular diseases can be prevented by addressing behavioral risk factors. The study on Cardiovascular Risk Behavior among adolescents of Higher Secondary School of Butwal Sub-Metropolitan City aimed to identify cardiovascular health risk behaviors among adolescents. Method: A descriptive Cross-sectional study design was used among 128 students aged 17 to 19 years and studying in class 12. A self-administered structured questionnaire was used for data collection. The collected data were entered and analyzed on SPSS version 22, and descriptive and inferential statistics were applied. Result: The mean age of respondents was 17.22±0.77 years. The cardiovascular risk behaviors was smoking 5(3.9%), tobacco use 4(3.1%), and alcohol consumption 16(12.5%) found among respondents. Furthermore, consumption of junk food 24 (18.8%), and screen time of more than two hours was found. The study found a significant association between alcohol consumption and ethnicity of respondents (0.002) and type of family (0.013). Similarly, the history of tobacco use was significantly associated with sex (p=0.041), and junk food consumption was associated (p=0.02) with the sex of respondents. Conclusion: Cardiovascular health risk behaviors such as smoking, tobacco use, alcohol intake, consumption of junk food, and long screen time were found, which indicates an alarming increase in the rate of mortality and morbidity. Therefore, it is needed to promote awareness about the importance of a healthy diet and the avoidance of risk behaviors.